Hubungan Penerapan Absensi Sidik Jari (Finger Print)Dengan Motivasi Dan Kinerja Karyawan (Studi Kasus Pada Fakultas Ekonomi Dan Bisnis, Universitas Muhammadiyah Surakarta - Jawa Tengah) - Widyastuti, Febriani; , M.Sholahuddin,SE.,Msi (2016)
This study aims to: the relationship between the application of finger print attendance program on motivation in FEB UMS and the relationship between the application of finger print attendance program of performance at the UMS FEB. This type of research uses explanatory research design. Explanatory re-search is a type of research that highlights the relationships between research vari-ables and test hypotheses. This study used a sample in this study were 35 employees and lecturers of the faculty population of 80 employees, with the consideration that to study a rep-resentative sample of at least 10 percent of the population. The analytical tool used in this study Spearman Rank correlation. Results of the analysis showed that the Spearman Rank Correlation Test that the Implementation Finger Print with Employee Motivation result of rhitung = 0.415> rtabel = 0.273, or a close value of 0.000 <0.05 then H1 be accepted so that there is a close relationship Application Program Attendance Finger Print with Employee Motivation. Based on results of this analysis indicate that the first hypothesis stating "Allegedly there is a close relationship between the variables Implementation Finger Print with employees Motivation Faculty of Economics and Business, University of Muhammadiyah Surakarta" unsubstantiated. Spear-man Rank Correlation test relating to the Implementation of Finger Print with Employee Performance results obtained from rhitung = 0,544> rtabel = 0.273, or a close value of 0.000 <0.05 then H2 be accepted so that there is a close relationship Implementation Finger Print with Performance employees. Based on results of this analysis indicate that the second hypothesis states "Allegedly there is a close relationship between the variables Implementation Finger Print with employee performance Faculty of Economics and Business, University of Muhammadiyah Surakarta" unsubstantiated.